2020
DOI: 10.2166/h2oj.2020.021
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of flood-prone areas using modified topographic index for a river basin

Abstract: The modified topographic index (TI m ) based on digital elevation models (DEMs) was employed to delineate floodprone areas in Mahanadi basin, India. TI m and flood inundation maps were compared to obtain the threshold (t) beyond which the area is assumed to be inundated by flood and the exponent of the TI m . Scale dependence was also investigated to evaluate the sensitiveness of spatial resolution of the DEMs. DEMs of five resolutions, namely, ASTER global, SRTM, GMTED2010 (30 arc-seconds), GMTED 2010 (15 arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Rejouanul [60] used Landsat imagery to calculate the area of waterlogged in Sadekira County using a supervised classification method. Alternatively, the DEM topographic index was utilized to delineate waterlogging-prone areas in the Mohanadi Basin, India [61]. A multifaceted fusion of topographic, subsurface, transportation and meteorological elements was used to derive waterlogging-prone areas using hydrologic analysis [62].…”
Section: Compared With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rejouanul [60] used Landsat imagery to calculate the area of waterlogged in Sadekira County using a supervised classification method. Alternatively, the DEM topographic index was utilized to delineate waterlogging-prone areas in the Mohanadi Basin, India [61]. A multifaceted fusion of topographic, subsurface, transportation and meteorological elements was used to derive waterlogging-prone areas using hydrologic analysis [62].…”
Section: Compared With Previous Studiesmentioning
confidence: 99%
“…A multifaceted fusion of topographic, subsurface, transportation and meteorological elements was used to derive waterlogging-prone areas using hydrologic analysis [62]. The study attributes waterlogging to a combination of topography, slope, water accumulation and land use [61,63,64]. Waterlogging management and resolution strategies focus on sponge cities, natural solutions, resilience concepts, and more [65][66][67].…”
Section: Compared With Previous Studiesmentioning
confidence: 99%
“…TI was modified and introduced as the modified topographic index (TI m ) (Manfreda et al, 2011). The DEM maps were examined with a spatial resolution of 30 Arc-S, 15 Arc-S, and 7.5 Arc-S to obtain the optimal threshold using TI m in the Mahanadi basin, India (Nagesh Kumar et al, 2021). Their results showed that increasing the spatial resolution of DEM maps causes increasing the accuracy of flood threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the geographic information system and remote sensing have led to the acceleration of production, processing, analysis, floods management, and high‐resolution spatial images of the Earth's surface (Demir & Kisi, 2016; Fu et al, 2020). The topographic index (TI) method uses Digital Elevation Model (DEM), soil moisture, and LULC for flood modeling (Nagesh Kumar et al, 2021). Increasing the spatial accuracy of DEM maps causes an increase in the accuracy of flood zoning and a decline in flood modeling error (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%